2010
DOI: 10.1016/j.bbrc.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol accumulation in Niemann Pick type C (NPC) model cells causes a shift in APP localization to lipid rafts

Abstract: It has been suggested that cholesterol may modulate amyloid-β (Aβ) formation, a causative factor of Alzheimer's disease (AD), by regulating distribution of the three key proteins in the pathogenesis of AD (β-amyloid precursor protein (APP), β-secretase (BACE1) and/or presenilin 1 (PS1)) within lipid rafts. In this work we tested whether cholesterol accumulation upon NPC1 dysfunction, which causes Niemann Pick type C disease (NPC), causes increased partitioning of APP into lipid rafts leading to increased CTF/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 25 publications
6
46
0
Order By: Relevance
“…Lipid rafts may also facilitate Aβ aggregation (Rushworth & Hooper, 2010) and extracellular Aβ internalization (Lai & McLaurin, 2010). Increased cholesterol accelerates APP localization into lipid rafts and enhances Aβ generation (Kosicek et al, 2010;Michikawa, 2003); consistent with observations that elevated dietary cholesterol uptake or hypercholesterolemia is associated with increased formation of amyloid plaques (Kivipelto et al, 2001). In addition, cholesterol depletion inhibits neuronal Aβ generation ; and cholesterol-reducing statin drugs appear to reduce the risk of dementia (Gibson Wood et al, 2003).…”
Section: The Risk Factors Of Apoe and Cholesterolsupporting
confidence: 77%
“…Lipid rafts may also facilitate Aβ aggregation (Rushworth & Hooper, 2010) and extracellular Aβ internalization (Lai & McLaurin, 2010). Increased cholesterol accelerates APP localization into lipid rafts and enhances Aβ generation (Kosicek et al, 2010;Michikawa, 2003); consistent with observations that elevated dietary cholesterol uptake or hypercholesterolemia is associated with increased formation of amyloid plaques (Kivipelto et al, 2001). In addition, cholesterol depletion inhibits neuronal Aβ generation ; and cholesterol-reducing statin drugs appear to reduce the risk of dementia (Gibson Wood et al, 2003).…”
Section: The Risk Factors Of Apoe and Cholesterolsupporting
confidence: 77%
“…In addition, a 3-fold increase of cholesterol was detected in the isolated lysosomal fractions from NPC1-null compared to CHOwt cells (p<0.01) ( Figure 1C). This result is in agreement with our previous work using this model (7)(8)(9). We next performed MS-based proteomic analysis of the isolated lysosomal fractions.…”
Section: Lysosomal Isolation From Npc1-null and Chowt Cells Using Thesupporting
confidence: 80%
“…To test these two possibilities we measured the levels of fluorescein signal in the cell lysate and in the medium 24 hours after initial uptake. We did not observe significant differences of the intracellular and Table 1 and Notably, in our previous studies we have substantially used this NPC disease cellular model to elucidate the molecular and cellular details of an AD-like phenotype in NPC (7)(8)(9)36). Based on our results we speculate that changes in the N-glycome of the lysosomal membrane proteins may contribute to lysosomal (dys)function in NPC disease.…”
Section: Lysosomal Isolation From Npc1-null and Chowt Cells Using Thementioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, changes in raft composition have been described for some lysosomal storage disorders such as Niemann-Pick type C [33], Gaucher disease type I [34], Sandhoff disease [35], Sanfilippo disease [36], neuronal ceroid lypofuscinosis [37], and Krabbe disease [38]. Whether lipid raft structure is altered in Fabry disease is not known, however recent studies have suggested that trafficking of the glycosphingolipid lactosylceramide and of the apical glycoprotein dipeptidylpeptidase IV are perturbed in fibroblasts of Fabry disease patients compared to control fibroblasts [39,40].…”
Section: Introductionmentioning
confidence: 99%